EFFECTS OF STEM-BARK EXTRACT OF OKOUBAKA AUBREVILLIE ON SOME VISCERAL ORGANS OF WISTAR RATS - Peter, Achukwu U; Silas, Ufelle A; Kenechukwu, Onyekwelu C; Millicent, Amadi N; Ngozika, Achukwu O; Francis, Amadi N (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Over the past two decades, there has been a tremendous increase in the use of herbal medicine; however, these herbs have not been properly evaluated to ascertain their effect on the body organs. Materials and Methods: Effects of stem bark extract of Okoubaka aubrevillie on some visceral organs were investigated in Wistar rats. For acute toxicity testing, Wistar rats (n=16), grouped into 4, (A-D) orally received graded doses of Okoubaka aubrevillie extract and deaths recorded within 24 hours. For sub-acute study, Wistar rats (n=20) grouped into 5, (A-E) orally received graded doses of Okoubaka aubrevillie extract for 31 days. Blood samples were collected from each rat through retro-orbital puncture for biochemical analysis. The liver, kidney and stomach were excised and processed for light microscopy. For toxin inhibition studies, Wistar rats (n=24) grouped into 6 (A-F), were used. Groups A-C and D-F orally received graded doses of Dichlorvos. Groups A-C further received Okoubaka aubrevillie extract while D-F received water and death records observed. Results: For acute toxicity testing, lethal dose (LD50) of 7500 mg/kg body weight was obtained from the inverse of the log-dose. Sub-acute studies revealed significantly elevated mean body weight in group A (210 ± 4.5 gram) compared to control (178 ± 5.0 gram), (p<0.05). Liver of rats in group A revealed some areas of moderate peri-portal lymphatic inflammation. Treated groups revealed intact architecture of liver, kidney and stomach. Conclusion: Okoubaka aubrevillie extract was found to be relatively safe for consumption and is capable of inhibiting toxins.